2020
DOI: 10.1155/2020/8828747
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of a Slope considering Two Reinforcement Processes

Abstract: The strength reduction method embedded in a distinct element code was used to analyse the stability of a slope in a coal mining area that had been reinforced twice, primarily with pile and retaining wall, followed by porous steel-tube bored grouting. For the primary reinforcement, the factor of safety was calculated, slip surface and failure mechanism were determined, and the damage phenomenon of primary reinforcement was analysed in detail. Failure time of slope without further strengthening was predicted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hong et al conducted stability analysis on the artificial steep slope at the tunnel exit and evaluated the effectiveness of four reinforcement schemes [15]. Chen W et al used the strength reduction method embedded with different unit codes to analyze the stability of a coal mine slope that underwent two rounds of reinforcement, and verified the instability of the slope during the initial reinforcement stage [16]. Lopez-Vinielles et al proposed a method that combines digital photogrammetry, satellite radar interferometry, and geomechanical modeling for remote analysis of slope instability in open-pit mining areas [17].…”
Section: Related Workmentioning
confidence: 99%
“…Hong et al conducted stability analysis on the artificial steep slope at the tunnel exit and evaluated the effectiveness of four reinforcement schemes [15]. Chen W et al used the strength reduction method embedded with different unit codes to analyze the stability of a coal mine slope that underwent two rounds of reinforcement, and verified the instability of the slope during the initial reinforcement stage [16]. Lopez-Vinielles et al proposed a method that combines digital photogrammetry, satellite radar interferometry, and geomechanical modeling for remote analysis of slope instability in open-pit mining areas [17].…”
Section: Related Workmentioning
confidence: 99%
“…The HIgh REsolution Slope Stability Simulator (HIRESSS) was used to model the outcomes, and then it was compared to a conventional, non-IoT based technique. www.ijacsa.thesai.org Models for analysis of submerged pools [30], use of random field Gaussian methods [31], blocky structure systems [32], near-surface rock strength slope analysis [33], and reinforcement learning models [34][35][36][37] are also used for high efficiency slope analysis. It can be observed that most of these models do not define sensor placement analysis, due to which their efficiency is limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fan et al used the large-scale shaking table test to study the dynamic response of slopes reinforced by double-row anti-slide piles and prestressed anchor cables, and discussed the influence of two anti-slide pile reinforcement measures on the dynamic response characteristics of slopes [15]. Chen et al, based on the strength reduction method, adopted piles, retaining walls, porous steel pipe grouting and other methods to consolidate an open-pit slope, and discussed the reinforcement effect of the slope and the feasibility of the reinforcement methods [16]. Wang et al used the finite element method to study the action mechanism of pile foundations in slopes, and studied the influence of the position and length of a pile foundation on the stability of an embankment [17].…”
Section: Introductionmentioning
confidence: 99%